Hemodynamic Evaluation of Type B Aortic Dissection Using Compressed Sensing Accelerated 4D Flow MRI - Kilinc, Ozden; Chu, Stanley; Baraboo, Justin; Weiss, Elizabeth K.; Engel, Joshua; Maroun, Anthony; Giese, Daniel; Jin, Ning; Chow, Kelvin; Bi, Xiaoming; Davids, Rachel; Mehta, Christopher; et al. (Journal of Magnetic Resonance Imaging, 2022)
Background: 4D Flow MRI is a quantitative imaging technique to evaluate blood flow patterns; however, it is unclear how compressed sensing (CS) acceleration would impact aortic hemodynamic quantification in type B aortic dissection (TBAD). Purpose: To investigate CS-accelerated 4D Flow MRI performance compared to GRAPP-accelerated 4D Flow MRI (GRAPPA) to evaluate aortic hemodynamics in TBAD. Study Type: Prospective. Population: Twelve TBAD patients, two volunteers. Field Strength/Sequence: 1.5T, 3D time-resolved cine phase-contrast gradient echo sequence. Assessment: GRAPPA (acceleration factor [R] = 2) and two CS-accelerated (R = 7.7 [CS7.7] and 10.2 [CS10.2]) 4D Flow MRI scans were acquired twice for interscan reproducibility assessment. Voxelwise kinetic energy (KE), peak velocity (PV), forward flow (FF), reverse flow (RF), and stasis were calculated. Plane-based mid-lumen flows were quantified. Imaging times were recorded. Tests: Repeated measures analysis of variance, Pearson correlation coefficients (r), intraclass correlation coefficients (ICC). P < 0.05 indicated statistical significance. Results: The KE and FF in true lumen (TL) and PV in false lumen (FL) did not show difference among three acquisition types (P = 0.818, 0.065, 0.284 respectively). The PV and stasis in TL were higher, KE, FF, and RF in FL were lower, and stasis was higher in GRAPPA compared to CS7.7 and CS10.2. The RF was lower in GRAPPA compared to CS10.2. The correlation coefficients were strong in TL (r = [0.781–0.986]), and low to strong in FL (r = [0.347–0.948]). The ICC levels demonstrated moderate to excellent interscan reproducibility (0.732–0.989). The FF and net flow in mid-descending aorta TL were significantly different between CS7.7 and CS10.2. Conclusion: CS-accelerated 4D Flow MRI has potential for clinical utilization with shorter scan times in TBAD. Our results suggest similar hemodynamic trends between acceleration types, but CS-acceleration impacts KE, FF, RF, and stasis more in FL. Evidence Level: 1. Technical Efficacy: Stage 2.
CRIS-Team Scopus Importer:2022-10-07
Keywords: 4D Flow; aorta; dissection; flow; hemodynamics; MRI